Utilization of Abandoned Customary Land: Reconstructing the Concept of Ihya' al-Mawat for Sustainable Economic Development (A Case Study in Nagari Bukit Sileh, Solok Regency) - Roni Marizal Putra; Endri Yenti (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The underutilization of customary land remains a persistent challenge in Indonesia’s Indigenous communities, particularly in Minangkabau, where communal land ownership is governed by customary law. Despite its substantial economic potential, considerable areas of customary land remain abandoned because of legal, institutional, social, and economic constraints. This study aimed to analyze customary land utilization in Nagari Bukit Sileh, Solok Regency, examine the relevance of Iḥyāʾ al-Mawāt to sustainable economic development, and formulate a reconstructive model of customary land management grounded in Islamic legal principles. A descriptive qualitative approach with a case study design was employed. Primary data were collected through field observations and semi-structured interviews, while secondary data were obtained from classical and contemporary Islamic legal literature. The data were analyzed through data reduction, data display, and conclusion drawing and verification, with source triangulation used to ensure data credibility. The findings indicate that customary land utilization in Nagari Bukit Sileh has not reached its full potential, as substantial areas remain unproductive because of interrelated legal, social, economic, and institutional constraints. From the perspective of Iḥyāʾ al-Mawāt, productive land use should be encouraged without altering the communal ownership status of customary land. Reconstructing this concept through muḍārabah and muzāraʿah contracts provides a relevant framework for sustainable economic development by improving community welfare, expanding economic opportunities, and preserving social and environmental balance. The study concludes that integrating Iḥyāʾ al-Mawāt with communal customary land governance offers an Islamic legal model for revitalizing abandoned land while protecting collective ownership. This model contributes to the development of more inclusive, productive, and sustainable customary land governance and rural economic development.